Analisis Prespektif Modal Sosial "Duit Ora Payu" Gerakan Sosial Menolak Jual Beli Suara di Desa Narukan - Arissy Jorgi Sutan; M Wira Anshori; Dinda Rosanti Salsa Bela; Azira Novia Rizal; Revi Jeane Putri; Uswatun Asiah (Nakhoda: Jurnal Ilmu Pemerintahan, 2025)
This study analyzes the social movement “duit ora payu” (money doesn’t work) as a grassroots rejection of vote buying in the Village Head Election (Pilkades) of Narukan Village, Rembang Regency. This phenomenon is significant because it presents an electoral anomaly in which local communities collectively resisted money politics, contributing to contemporary studies on village democracy and electoral integrity. Using a descriptive qualitative approach, this research draws on literature studies and digital data to examine the dynamics surrounding the election. The findings show that the high level of social capital possessed by the elected candidate, Gus Faruq, built through strong social networks, public trust in integrity, and sincere civic engagement, became the decisive factor in defeating opponents suspected of distributing money in a structured manner. His close relationship with prominent religious figures, especially Gus Baha, further strengthened moral credibility and reinforced anti-money politics norms in the community. The study concludes that value-based social capital can effectively counteract corrupt electoral practices and offers a replicable model for promoting clean grassroots elections.